2011
DOI: 10.1002/jbm.a.33225
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral interface regeneration of the rabbit knee with macroscopic gradients of bioactive signals

Abstract: To date, most interfacial tissue engineering approaches have utilized stratified designs, in which there are two or more discrete layers comprising the interface. Continuously-graded interfacial designs, where there is no discrete transition from one tissue type to another, are gaining attention as an alternative to stratified designs. Given that osteochondral regeneration holds the potential to enhance cartilage regeneration by leveraging the healing capacity of the underlying bone, we endeavored to introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 41 publications
1
69
0
Order By: Relevance
“…Hence, the current study investigated the potential of implanting gradient scaffolds engineered to recruit stem cells from the bone marrow into large defects for the purpose of regenerating bone and cartilage. We have previously investigated the potential of the microsphere-based scaffolds with gradients of growth factors, raw materials and combinations for both osteochondral tissue engineering in vitro and osteochondral regeneration in vivo in rabbits [10,20,[35][36]. This is our first report on the long-term outcome of the implant of these gradient scaffolds in critical size osteochondral defects (6 mm diameter × 6 mm depth) in a large animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the current study investigated the potential of implanting gradient scaffolds engineered to recruit stem cells from the bone marrow into large defects for the purpose of regenerating bone and cartilage. We have previously investigated the potential of the microsphere-based scaffolds with gradients of growth factors, raw materials and combinations for both osteochondral tissue engineering in vitro and osteochondral regeneration in vivo in rabbits [10,20,[35][36]. This is our first report on the long-term outcome of the implant of these gradient scaffolds in critical size osteochondral defects (6 mm diameter × 6 mm depth) in a large animal model.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Dormer and co-workers reported the use of a miniature bioactive plug, which was constructed from PLGA microspheres with a gradient transition between chondrogenic and osteogenic growth factors, to repair small mandibular condylar defects in New Zealand white rabbits. After six weeks, histology and magnetic resonance imaging (MRI) showed that the implants provided support for the neosynthesized tissue regeneration within the defects (Dormer et al, 2012). Yu et al (2011) combined distraction ontogenesis with tissue engineered cartilage to reconstruct condylar osteochondral defects in goats.…”
Section: Cartilage Tissue Engineering In Mandibular Condylementioning
confidence: 99%
“…The major ECM components contained in these sub-tissues are collagen type II and glycosaminoglycans; collagen type I, glycosaminoglycans, minerals; and collagen type I and minerals, respectively (Table 1). Another school of thought for the hierarchical organization of the cartilage-bone interface is the belief of graded change in the composition of ECM components [6][7][8][9]. Although the compartmental organization approach for cartilage-bone interface components has been dominant for years [5,10], recent studies characterizing cartilagebone, as well as tendon-bone, interface at microscopic dimensions found that mineral composition is changing gradually across the interface [4,11,12].…”
Section: Function Composition and Structurementioning
confidence: 99%